The 2021 Conference on Artificial Life 2021
DOI: 10.1162/isal_a_00371
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early-death on Phenotypically Plastic Robots that Evolve in Changing Environments

Abstract: In this work, we evolve phenotypically plastic robots -robots that adapt their bodies and brains according to environmental conditions -in changing environments. In particular, we investigate how the possibility of death in early environmental conditions impacts evolvability and robot traits. Our results demonstrate that early-death improves the efficiency of the evolutionary process for the earlier environmental conditions. On the other hand, the possibility of early-death in the earlier environmental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…As an extension of this work, it might be of interest to experiment with additional representations, e.g., based on neural cellular automata, and to take into account environmental feedback [24] in development. Moreover, the concept of early mortality [16] could be introduced in our framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an extension of this work, it might be of interest to experiment with additional representations, e.g., based on neural cellular automata, and to take into account environmental feedback [24] in development. Moreover, the concept of early mortality [16] could be introduced in our framework.…”
Section: Discussionmentioning
confidence: 99%
“…Some developmental representations have become popular [14,15], but they have been mostly used for morphogenesis only. One instance of a development study has demonstrated the benefits of environmental regulation for lifetime phenotypic plasticity so that bodies and brains of robots could adapt in response to environmental changes [16,17]. Another approach experimented with reconfigurable robots that relied on manually designed bodies [18].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…However, scarce attention has been paid to the environmental regulation of phenotypic plasticity. Whereas only a few examples of studies related to development and phenotypic plasticity are found in the literature [21][22][23][24][25][26][27], none of these examine the costs of plasticity. Here, a hypothesis is posited that despite the potential of phenotypic plasticity, its benefits may be potentially undermined by plasticity-related genetic costs.…”
Section: Introductionmentioning
confidence: 99%